Cytomegalovirus infection in a T-cell lymphoma patient presenting with multiple gastrointestinal ulcers: a case report - Tao, Jin; Lin, Xian Yi; Tsia Hin Fong, Christ-Jonathan; Wen, Zhuo Fu; Chen, Jian Ning; Liang, Qiong; Lin, Qu; Wu, Bin (Endoscopy International Open, 2019)
Background and study aims Gastrointestinal ulcers are responsible for a wide spectrum of diseases. Infection, drug-induced enteritis, malignancy, vasculitis and Inflammatory bowel disease are the most common causes; their clinical expression often varies according to the site and severity of intestinal involvement. We report on a 68-year-old male presenting with dyspepsia and melena and multiple gastrointestinal ulcers on endoscopy. We could not establish diagnosis of peripheral T-cell lymphoma not otherwise specified (PTCL-NOS) despite multiple biopsies taken on several endoscopic sessions, and cytomegalovirus (CMV) infection was documented by presence of inclusion bodies on pathology. The immunohistochemical study showed a mixture of B lymphocytes and predominantly T lymphocytes, negative for cluster of differentiation (CD)7. Southern blot gene rearrangement was positive for T-cell receptor beta. Our patient eventually expired from a massive gastrointestinal hemorrhage following four cycles of chemotherapy. We wish to emphasize that a CMV infection, as a comorbidity, can potentially mask and delay diagnosis of PTCL-NOS, especially in cases with aberrant immunophenotype presentation.